Valorization of the Biological Activity of Euphorbia hirta - Nadir El Mostafa (International Journal of Pharmaceutical & Biological Archive, 2024)
Aim: The main objective of our study it to valorization of the biological activity of euphorbia hirtathe. Material & Methods: Phytochemical analysis of Euphorbia hirta revealed a variety of compounds, including saponins, polyphenols, flavonoids, tannins, terpenoids, coumarins, and cardiac glycosides. Quantitative measurements indicated that the methanolic extract from the roots is particularly rich in phenolic compounds, with a concentration of 128.45 ± 5.1 micrograms GAE/mg of extract. Conversely, the methanol extract from the stems had the highest flavonoid content, at 36.11 ± 0.45 micrograms QE/mg of extract. Result: The antioxidant capacity of the polar extracts was evaluated using the DPPH method, showing that the root methanol extract exhibited significant antioxidant activity, with an IC50 value of 07.04 ± 0.14 micrograms/ml. Conlusion: Additionally, a correlation was noted between the levels of polyphenols and the concentration of phenolic compounds present.